A Clade II‐D Fungal Chimeric Diterpene Synthase from Colletotrichum gloeosporioides Produces Dolasta‐1(15), 8‐diene. Issue 48 (26th October 2018) - Bian, Guangkai; Rinkel, Jan; Wang, Zhangqian; Lauterbach, Lukas; Hou, Anwei; Yuan, Yujie; Deng, Zixin; Liu, Tiangang; Dickschat, Jeroen S.
Abstract: Based on a terpenoid overproduction platform in yeast for genome mining, a chimeric diterpene synthase from the endophytic fungus Colletotrichum gloeosporioides ES026 was characterized as the (5 R, 12 R, 14 S )‐dolasta‐1(15), 8‐diene synthase. The absolute configuration was independently verified through the use of enantioselectively deuterated terpene precursors, which unequivocally established the predicted C1‐III‐IV cyclization mode for this first characterized clade II‐D enzyme. Extensive isotopic labeling experiments and isolation of the intermediate (1 R )‐δ‐araneosene supported the proposed cyclization mechanism. Abstract : The missing link : Fungal chimeric diterpene synthases with prenyltransferase and terpene synthase domains fall into two clades (I+II) with six subclades (A–F). The present study reports the characterization of the first clade II‐D enzyme, the structures of its products, and the cyclization mechanism. The observed 12 R configuration reveals a uniform stereochemistry at this carbon for all clade II enzyme products.